From Namibia with Love - the dissertation paper a reflective essay supporting the documentary film 'From Namibia with Love'. With special references from the director's and editor's perspective on making a politically sensitive documentary film - Merilainen, Laura (Centre for Film and Media Studies, 2015)
Includes abstract.